Development of the Potential of Tourism Villages in Increasing Community Employment from an Islamic Economic Perspective - Rahayu, Riska Aditiya; Abizar; Mawardi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
Sumber Agung Village Tourism in Bandar Lampung City is a small example of the many efforts to develop the creative economy carried out by the community. The aim of this research is to determine the potential development of tourist villages in increasing community employment according to Islamic economic views. The research method is field research. Data collection techniques are carried out through Interview, Observation and Documentation methods. The research results show that management of this tourist attraction is community-based, but that does not mean without supervision from the manager. Management here uses the POAC principle (Planning, Organizing, Actuating and Controlling). The economic activities carried out by the community due to tourism are in accordance with Islamic economics.